ANALYSIS OF PROVIDER SATISFACTION TOWARD THE PERFORMANCE OF GOVERNMENT PROCUREMENT SERVICES IN GORONTALO PROVINCE USING IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Azis Rachman; Rachmat Taufik Usman; Nur Fathimatuzzahro Putri Salsabila Kaharu; Fatmanda Tristika Meylia Datu (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This study aims to analyze provider satisfaction with the performance of government goods and services procurement services in Gorontalo Province using a qualitative Importance Performance Analysis (IPA) approach. The study is motivated by the critical role of procurement service quality in supporting the principles of good governance, particularly transparency, accountability, and efficiency. The research employs a descriptive qualitative approach, with data collected through in-depth interviews involving informants who have direct experience in procurement processes. Data were analyzed thematically using the IPA framework to identify key dimensions of importance, performance, service gaps, and priority areas for improvement. The findings indicate that transparency and accountability are the most critical factors influencing provider satisfaction, followed by service responsiveness, timeliness, and the competence of human resources. Although the overall performance of procurement services is perceived as satisfactory, gaps remain in responsiveness, timeliness, and human resource capacity. These gaps are primarily influenced by limitations in human resources, regulatory complexity, and suboptimal system support. This study emphasizes that improving provider satisfaction is not solely dependent on system digitalization, but also on the quality of service implementation and procurement governance. Therefore, improvement efforts should focus on service attributes that are highly important yet underperforming, particularly through enhancing human resource capacity, strengthening transparency and accountability, and improving service interaction quality. This study contributes empirically to the development of procurement policies that are oriented toward service quality and user needs.